2009
DOI: 10.1029/2008jc004925
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the initial errors that cause a significant “spring predictability barrier” for El Niño events

Abstract: Within the Zebiak‐Cane model, we identify two types of initial errors that have significant season‐dependent evolutions related to the spring predictability barrier (SPB) for El Niño events. One type includes the sea surface temperature anomaly (SSTA) errors that have a zonal dipolar pattern with positive anomalies in the central equatorial Pacific and negative ones in the eastern equatorial Pacific; the other type consists of the SSTA errors with a spatial structure opposite to that of the former type, the zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
87
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 34 publications
4
87
0
1
Order By: Relevance
“…Quite a few studies have explored the important role of the initial errors in ENSO prediction uncertainties (Chen et al 1995(Chen et al , 2004Moore and Kleeman 1996;Mu et al 2007;Thompson 1998;Xue et al 1997a, b) or emphasized the importance of the accuracy of initial analysis fields in improving ENSO forecast skill (Keenlyside et al 2005;Zheng et al 2006Zheng et al , 2007Zhu et al 2017). Moreover, recent studies showed that the initial errors with particular spatial structures cause much larger prediction uncertainty for ENSO (Mu et al 2007;Yu et al 2009;Duan et al 2009;Duan and Hu 2016). Specifically, Duan et al (2009) pointed out that the initial errors with a dipole structure of sea surface temperature anomalies (SSTAs) along the tropical Pacific are most likely to cause a significant spring predictability barrier (SPB) phenomenon for El Niño events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite a few studies have explored the important role of the initial errors in ENSO prediction uncertainties (Chen et al 1995(Chen et al , 2004Moore and Kleeman 1996;Mu et al 2007;Thompson 1998;Xue et al 1997a, b) or emphasized the importance of the accuracy of initial analysis fields in improving ENSO forecast skill (Keenlyside et al 2005;Zheng et al 2006Zheng et al , 2007Zhu et al 2017). Moreover, recent studies showed that the initial errors with particular spatial structures cause much larger prediction uncertainty for ENSO (Mu et al 2007;Yu et al 2009;Duan et al 2009;Duan and Hu 2016). Specifically, Duan et al (2009) pointed out that the initial errors with a dipole structure of sea surface temperature anomalies (SSTAs) along the tropical Pacific are most likely to cause a significant spring predictability barrier (SPB) phenomenon for El Niño events.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies showed that the initial errors with particular spatial structures cause much larger prediction uncertainty for ENSO (Mu et al 2007;Yu et al 2009;Duan et al 2009;Duan and Hu 2016). Specifically, Duan et al (2009) pointed out that the initial errors with a dipole structure of sea surface temperature anomalies (SSTAs) along the tropical Pacific are most likely to cause a significant spring predictability barrier (SPB) phenomenon for El Niño events. Duan and Wei (2012) further showed the existence of these initial errors in realistic predictions for El Niño.…”
Section: Introductionmentioning
confidence: 99%
“…This clarification illustrates why we emphasize that a significant SPB entails not only a large prediction error but also a prominent seasonality of error growth. With this description of the 'significant SPB', Duan et al (2009) and Yu et al (2009) used the Zebiak-Cane model (Zebiak and Cane, 1987) to study the spatial characteristics of initial errors that cause 'a significant SPB' for ENSO events by performing perfect model predictability experiments with the approach of conditional nonlinear optimal perturbation (CNOP; Mu et al, 2003;Duan et al, 2004Duan et al, , 2008Mu and Zhang, 2006;Duan and Mu, 2006). CNOP represents the initial error that induces the largest prediction error at the prediction time and has the potential for yielding a significant SPB (Mu et al, 2007a(Mu et al, , 2007bYu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…CNOP represents the initial error that induces the largest prediction error at the prediction time and has the potential for yielding a significant SPB (Mu et al, 2007a(Mu et al, , 2007bYu et al, 2009). Using the CNOP method, Duan et al (2009) and Yu et al (2009) identified two types of CNOP-type initial errors that cause a significant SPB for El Nino events. One type possesses an SSTA component that has a largescale zonal dipolar pattern with positive anomalies in the central equatorial Pacific and negative anomalies in the eastern equatorial Pacific; it tends to cause El Nino events to be under-predicted through spring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation